Transcatheter treatment of heart failure with preserved or mildly reduced ejection fraction using a novel interatrial implant to lower left atrial pressure. (24th June 2014) - Søndergaard, Lars; Reddy, Vivek; Kaye, David; Malek, Filip; Walton, Antony; Mates, Martin; Franzen, Olaf; Neuzil, Petr; Ihlemann, Nikolaj; Gustafsson, Finn
<x xml:space="preserve">Abstract</x> Background Heart failure with preserved or mildly reduced ejection fraction (HFpEF) is common and, to date, therapeutic options are limited. Increased left atrial pressure is a key contributor to the symptoms associated with HFpEF, particularly during physical activity. We report the 30‐day outcome of patients treated with a novel device intended to lower left atrial pressure by creating an 8 mm permanent shunt in the atrial septum. Methods and results Eleven patients were enrolled in the pilot trial. Key inclusion criteria were: EF >45%; baseline PCWP ≥15 mmHg (rest), or ≥ 25 mmHg (exercise); and ≥1 hospitalization for heart failure within the past 12 months, or persistent NYHA class III/IV for at least 3 months. Mean age, LVEF, and NYHA class were 70 ± 12 years, 57 ± 9%, and 3.2 ± 0.4, respectively. Most patients had significant co‐morbidities. The interatrial septal device (IASD) device was implanted using percutaneous trans‐septal access via the femoral vein. The device was successfully implanted in all patients. At 30 days, LV filling pressures were significantly reduced by 5.5 mmHg (19.7 ± 3.4 vs. 14.2 ± 2.7; P = 0.005), and NYHA class was improved by two classes in two patients, one class in five patients, and worsened by one class in one patient. No patient developed pulmonary hypertension. Two serious adverse events occurred; heart failure re‐hospitalization, and implant malposition successfully treated with a new device. Conclusion Contemporary management of HFpEF patients is confounded by the lack of effective therapies. The use of a device‐based approach to reduce left atrial pressure provides a novel means to improve haemodynamic and symptomatic status in HFpEF patients and warrants further investigation.